2015
DOI: 10.1111/jdv.13477
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of XPC Lys939Gln polymorphism and melanoma susceptibility

Abstract: Our pooled data suggest that there was no evidence for a major role of XPC Lys939Gln polymorphism in the pathogenesis of melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Articles selected [2,7,10,14,[18][19][20][21][22][23] for qualitative assessment are presented in Table 1. After 504 abstracts screening, 13 full-text articles were assessed for eligibility, and 3 of them were excluded: one article was focused only on the association of XP with gastric cancer, one did not fit the topic and represented a limit of the online database search, one article had a control study design, so was excluded having low evidence level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Articles selected [2,7,10,14,[18][19][20][21][22][23] for qualitative assessment are presented in Table 1. After 504 abstracts screening, 13 full-text articles were assessed for eligibility, and 3 of them were excluded: one article was focused only on the association of XP with gastric cancer, one did not fit the topic and represented a limit of the online database search, one article had a control study design, so was excluded having low evidence level.…”
Section: Resultsmentioning
confidence: 99%
“…With specific regard to melanoma occurrence, Jiang et al [ 23 ] investigated the correlation with a single XPC polymorphism, but the study failed to prove a strong association and was based on unadjusted estimates for age, gender, and nationality, so compromising the quality of evidence.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, Zhou et al, in a meta-analysis of seven studies (with 3,971 cases and 5,873 controls) have reported that the XPC Lys939Gln polymorphism was not significantly associated with CMM risk under all five genetic models (29). Jiang et al, in a more recently published meta-analysis with eight studies of 4,631 cases and 5,111 controls have found also negative results (30). The current meta-analysis has a number of strengths when compared to the previous meta-analyses.…”
Section: Subgroupmentioning
confidence: 99%